The effect of brain breaks on motivation to physical activity, sustained attention, short-term memory, and academic performance among malay primary school children - Bakar, Mawar Siti Hajar Abu (2020)
Brain breaks is a physical activity (PA) video that is used to stimulate student’s health and learning and was designed for school settings. The purpose of this study was to measure the effects of brain-breaks on motives of participation in PA, sustained attention, short-term memory, and academic performance among Malay primary school children in Kelantan. The intensity of brain breaks implemented was low to moderate intensity. A total of 159 male and 176 female children aged 10 to 11 years old (mean age = 10.51 ± 0.50) from two schools in Kelantan were recruited in this study. Purposive sampling was used to divide the children into intervention (n = 183) and control (n = 152) groups. The brain breaks intervention was conducted one to three times per week for four months with each session lasting 15-30 minutes. The instruments used were PA and Leisure Motivation Scale Youth-Malay version (PALMS-Y-M), Digit Span Test (DST), Digit Vigilance Test (DVT) and Average Grade Score (AGS). These tests were carried out at two time-points, pre- and post-tests. Mixed analysis of variance (ANOVA) was used to analyse the data. The results showed significant changes in PA motives for enjoyment, F (1, 243) = 5.162, p-value = 0.024; appearance, F (1, 243) = 3.998, p-value = 0.047; psychological, F (1, 243) = 6.243, p-value = 0.013; sustained attention for numbers 6: total time F (1, 332) = 8.151, p-value = 0.005; and 9: total time F (1, 327) = 9.778, p-value = 0.002 and frequency of error made: F (1, 329) = 38.725, p-value < 0.001; short-term memory F (1, 301) = 38.381, p-value < 0.001. In conclusion,brain breaks was successful in improving children’s short-term memory and sustained attention while maintaining motives for PA participation. Future research should consider adding other tests to measure the cognitive domains of students for a more comprehensive insight.